Посогите срочно!!!!!!!
а) х(х-1)-х(х-3)=12
б)(х+1)(х+2)-х^2=5х+4
в) (х-4)^2 = х^2 -16
г) (х+ 1)^2 =х^2 +1

2

Ответы и объяснения

2014-04-14T19:30:55+04:00
A) х(х-1)-х(х-3)=12
 x^{2} -x- x^{2} -3x=12
-4x=12
x=-3
б)(х+1)(х+2)-х^2=5х+4
 x^{2} +2x+x+2- x^{2} =5x+4
-2x=2
x=-1
в) (х-4)^2 = х^2 -16
 x^{2} -8x+16= x^{2} -16
-8x=-32
x=4
г) (х+ 1)^2 =х^2 +1
 x^{2} +2x+1= x^{2} +1
2x=0
x=0
Лучший Ответ!
2014-04-14T19:31:08+04:00
А) х в квабрате-х-х в квадрате+3х=12 2х=12 х=12:2 х=6 б)х в квадрате+2х+х+2-х в квадрате=5х+4 3х+2=5х+4 3х-5х=4-2 -2х=2 х=2:(-2) х=-1 в)х^2-8х+16=х^2-16 х^2-х^2-8х=-16-16 -8х=-32 х=-32:(-8) х=4 г)х^2+2х+1=х^2+1 2х=2 х=2:2 х=1